2022
DOI: 10.3390/bs12100399
|View full text |Cite
|
Sign up to set email alerts
|

The Individuals’ Willingness to Get the Vaccine for COVID-19 during the Third Wave: A Study on Trust in Mainstream Information Sources, Attitudes and Framing Effect

Abstract: Different inner and external determinants might explain an individual’s willingness to get the vaccine for COVID-19. The current study aims at evaluating the effects of trust in mainstream information sources on individuals’ willingness to get the vaccine and the moderator role of the message framing. Six hundred and thirty-four participants (68.5% females and 31.5% males) were enrolled in an online survey. Participants filled out a questionnaire assessing: trust in mainstream information sources and vaccinal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Two studies demonstrated the moderating effect of self-efficacy towards vaccine immunization on the relationship between fear appeals and vaccination intentions [ 25 , 50 ]. Trust-related variables, such as trust in family physicians [ 26 ] and trust in vaccine benefits [ 32 ], also moderated the impact of fear appeals on vaccination intentions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies demonstrated the moderating effect of self-efficacy towards vaccine immunization on the relationship between fear appeals and vaccination intentions [ 25 , 50 ]. Trust-related variables, such as trust in family physicians [ 26 ] and trust in vaccine benefits [ 32 ], also moderated the impact of fear appeals on vaccination intentions.…”
Section: Resultsmentioning
confidence: 99%
“…Other moderators related to risks, benefits, and efficacy [ 16 , 23 , 25 , 39 , 42 , 45 , 50 , 58 ]. Some moderators relate to an individual’s past behavior [ 42 , 51 , 60 ], baseline intentions [ 14 ], self-efficacy [ 25 , 39 ], trust [ 26 , 32 , 39 ], familiarity with the vaccine or its side effects [ 13 , 14 ], anti-vax attitudes [ 55 ], psychological uncertainty [ 24 ], avoidance motivation [ 51 ], and issue relevance [ 61 ]. Finally, other moderators investigated so far include visual attention [ 47 ]), social media likes [ 50 ], and social norms [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Before COVID-19, studies indicated that the crux of the vaccination issue may have been trust or distrust in governmental and health institutions [25]. During COVID-19, a 2021 study indicated that increased trust in health experts was an important predictor of receiving a vaccine [26], while a 2022 study suggested that information from regulated sources was associated with individual health choices [27].…”
Section: Discussionmentioning
confidence: 99%
“…In the field of behavioral science, framing effects are often used to influence individual decision-making and behavioral preferences [26,27]. For example, by providing individuals with information framed around the benefits and public good nature of vaccines, it is possible to increase residents' intentions to get vaccinated [28]. Furthermore, framing effects are also widely designed to influence public opinion.…”
Section: Attribute Framing Effect and Its Impact On Persuasionmentioning
confidence: 99%